KOMPETENSIÂ PEDAGOGISÂ GURUÂ DALAMÂ PENGEMBANGANÂ SOSIALÂ EMOSIONALÂ ANAKÂ USIAÂ DINIÂ PADAÂ GUGUSÂ SEKOLAHÂ 11Â ARJOWINANGUNÂ KOTAÂ MALANG - rina rinawijayanti; muhammad akbar (Universitas Muhammadiyah Surabaya, 2016)
ThisÂ studyÂ wasÂ conductedÂ toÂ determineÂ (1)Â theÂ businessÂ conductedÂ byÂ theÂ teacherÂ to provideÂ theÂ infrastructureÂ basisÂ forÂ developmentÂ ofÂ socialâ€emotionalÂ earlyÂ childhoodÂ (2) theÂ learningÂ processÂ forÂ theÂ developmentÂ ofÂ socialâ€emotionalÂ alreadyÂ implemented teacherÂ atÂ schoolÂ (3)Â theÂ monitoringÂ andÂ evaluationÂ ofÂ developmentÂ capabilitiesÂ socialâ€emotionalÂ earlyÂ childhoodÂ teachersÂ inÂ theÂ schoolÂ haveÂ beenÂ implemented.Â ThisÂ studyÂ uses aÂ qualitativeÂ caseÂ studyÂ method,Â andÂ SpradleyÂ modelsÂ usingÂ analyticalÂ techniques.Â Based onÂ theÂ researchÂ conducted, theÂ researchÂ aspectsÂ ofÂ theÂ provisionÂ ofÂ infrastructureÂ facilities basicÂ socialÂ developmentÂ emotionalÂ earlyÂ childhoodÂ are:Â (1)Â teachersÂ doÂ notÂ haveÂ a descriptionÂ ofÂ theÂ toolsÂ forÂ socialÂ developmentÂ emotionalÂ earlyÂ childhood,Â (2)Â development ofÂ socialÂ skillsÂ emotionalÂ earlyÂ childhoodÂ wasÂ centeredÂ onÂ theÂ teacher,Â (3)Â emotionalÂ social learningÂ toolsÂ thatÂ haveÂ notÂ beenÂ revitalized.Â InÂ theÂ aspectÂ ofÂ theÂ processÂ andÂ strategyÂ forÂ theÂ establishmentÂ ofÂ socialÂ andÂ emotionalÂ learning,Â isÂ onlyÂ focusedÂ onÂ imitationÂ and habituationÂ andÂ thereÂ hasÂ beenÂ noÂ specificÂ programÂ ofÂ habituationÂ behaviorÂ withÂ the specificÂ objectiveÂ ofÂ socialÂ aspectsÂ ofÂ emotionalÂ developmentÂ ofÂ youngÂ children.Â WhileÂ the monitoringÂ andÂ evaluationÂ aspects:Â (1)Â monitoringÂ andÂ evaluationÂ effortsÂ areÂ notÂ focused onÂ theÂ child,Â butÂ theÂ endingÂ orÂ theÂ resultÂ ofÂ imitationÂ thatÂ hasÂ beenÂ done,Â (2)Â monitoring andÂ evaluationÂ ofÂ socialÂ emotionalÂ learningÂ onlyÂ atÂ theÂ endÂ orÂ summarizeÂ theÂ behaviorÂ of pupils.Â (3)Â psikotesÂ AUDÂ neverÂ becomeÂ referenceÂ materialÂ preparation ofÂ theÂ learning program.Â (4)Â monitoringÂ andÂ evaluationÂ ofÂ socialÂ emotionalÂ learningÂ onlyÂ takeÂ placeÂ if thereÂ areÂ obstaclesÂ orÂ disputesÂ pupil.